Levels of uric acid in erectile dysfunction of different aetiology. (3rd July 2018) - Barassi, Alessandra; Corsi Romanelli, Massimiliano Marco; Pezzilli, Raffaele; Dozio, Elena; Damele, Clara Anna Linda; Vaccalluzzo, Liborio; Di Dario, Marco; Goi, Giancarlo; Papini, Nadia; Massaccesi, Luca; Colpi, Giovanni Maria; Melzi d'Eril, Gian Vico
Abstract: Erectile dysfunction is a common disease characterized by endothelial dysfunction. The aetiology of ED is often multifactorial but evidence is being accumulated in favor of the proper function of the vascular endothelium that is essential to achieving and maintaining penile erection. Uric acid itself causes endothelial dysfunction via decreased nitric oxide production. This study aims to evaluate the serum uric acid (SUA) levels in 180 ED patients, diagnosed with the International Index of Erectile Function-5 (IIEF-5) and 30 non-ED control. Serum uric acid was analyzed with a commercially available kit using ModularEVO (Roche, Monza, Italy). Within-assay and between-assay variations were 3.0% and 6.0%, respectively. Out of the ED patients, 85 were classified as arteriogenic (A-ED) and 95 as non-arteriogenic (NA-ED) with penile-echo-color-Doppler. Uric acid levels (median and range in mg/dL) in A-ED patients (5.8, 4.3–7.5) were significantly higher ( p  < .001) than in NA-ED patients (4.4, 2.6–5.9) and in control group (4.6, 3.1–7.2). There was a significant difference ( p  < .001) between uric acid levels in patients with mild A-ED (IIEF-5 16–20) and severe/complete A-ED (IIEF-5 ≤ 10) that were 5.4 (range 4.3–6.5) mg/dL and 6.8 (range 6.4–7.2) mg/dL, respectively. There was no difference between the levels of uric acid in patients with different degree of NA-ED. Our findings reveal that SUA is a marker of ED but only of ED of arteriogenic aetiology.